(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2023)
Textual production in general has been a very addressed theme since all times and much has been published about the classes of "teaching" to write; however, this activity is one of the most difficult for teachers of pre-university education when teaching them. Although some of the factors expressed by teachers are real barriers affecting the production of quality texts by students at this level, there are methodological deficiencies in the teaching of this important component which, if resolved in the classes taught in Upper Secondary Education, would obtain superior results, not only in their examinations, but in their training as human beings. The article bases essential elements for the improvement of the classes of production of texts in its three moments: orientation, execution and revision, in the subject Spanish-Literature. Theoretical methods (analysis-synthesis, induction-deduction, documentary analysis) and empirical methods (scientific observation) were applied for the development of the research. The main results were that students develop skills for the production of written texts, and the interest in reading is emphasized, which favors their integral formation. The document becomes a tool for pre-university teachers that contributes to the improvement of their classes.